Feasibility and effects of horticultural activities on frailty, physical function, and quality of life among older adult residents in nursing homes: a quasi-experimental study - Wang, Jingwen; Niu, Xiaoyu; Guo, Ruru; Liu, Nana; Zhang, Weihong; Zhao, Mingli; Wang, Jingjing (Frontiers in Public Health, 2025)
ObjectivesThe aim was to evaluate the effectiveness of a horticultural activity intervention programme for improving frailty status, physical performance, and quality of life among frail older adult residents in nursing homes in Henan.DesignA quasi-experimental design was employed.ParticipantsTwo nursing homes were selected through convenience sampling and were assigned to the intervention or control group via a random lottery. A total of 92 participants were recruited for this study, with 46 participants from the intervention institution and 46 participants from the control institution, on the basis of predefined inclusion and exclusion criteria.MethodsBoth groups participated in regular nursing home activities. The intervention group additionally partook in a 6-month horticultural activity programme. Assessments of frailty, physical performance, and quality of life were assessed at baseline, 3 months, and 6 months post-intervention; validated instruments, including the Tilburg Frailty Indicator (TFI), the Chinese-Modified Physical Performance Test (CM-PPT), and the 12-Item Short Form Health Survey (SF-12), were used.ResultsCompared with the control group, the intervention group demonstrated potential improvements in frailty (TFI scores), physical performance, and dimensions of quality of life, including general health, mental health, and physical health. These effects were supported by significant between-group, time, and interaction effects (p < 0.05).ConclusionHorticultural activities may contribute to improvements in frailty, physical function, and quality of life in frail older adult residents in nursing homes, supporting the development of targeted interventions for this population. Future studies with larger sample sizes and subgroup analyses are recommended to compare effects across populations.